Financial management and policy - Van Horne, James C. (Englewood Cliffs, N.J. : Prentice Hall, 1992)
This book Financial Management and Policy provides three things. First, by developing an understanding of the rapidly evolving and exciting theory of finance, it enables readers to evaluate how close the firm's investment, financing, and dividend decisions come to an objective of maximizing shareholder wealth. Second, it familiarizes readers with the ways in which analytical techniques are applied to a variety of financial issues. Third, it supplies the institutional material necessary for a solid understanding of the environment in which financial decisions are made.
Includes bibliographical references and index.
hbb 04/07/2019
Loans
Keywords: Corporations